A systematic review of lived experience and coping styles among survivors of traumatic brain injury (TBI) - Abdul Rashid, Nor’ain; Lee, Khuan; Baharom, Anisah; Arshad, Mohd Mursyid (ASEAN Neurological Association, 2021)
Background & Objective: Throughout recovery, patients with traumatic brain injury (TBI) demonstrate physical, functional, cognitive, and psychosocial problems. The aim of this article was to review the literature regarding the lived experience and coping styles among TBI survivors. Method: The review was guided by the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) statement. The literature search was conducted using three different electronic databases, namely Scopus, CINAHL, and Ovid-Medline. In quantitative studies, a critical appraisal guide provided by Coughlan, Cronin and Ryan (2007) was used. Meanwhile, empirical studies of the qualitative studies were guided by the Joanna Briggs Institute (JIB) Critical Appraisal Tools for Reporting Qualitative Research. Result: There were 13 articles reviewed, four of them were quantitative studies and nine were qualitative studies. Most of the articles showed that TBI survivors faced problems in terms of emotional, behavioral, cognitive, and functional aspects, as well as quality of life. For the young TBI survivors, they have had to cope with academic challenges such as attention deficit and poor academic performance. For TBI survivors and partners, they also faced intimate relationship problems. Various coping practices were applied to regain their normal life. Some of the survivors used passive approach like avoidance and isolation. Some of the survivors applied religious coping methods to keep them feeling positive. Conclusion: This review confirmed the different dimensions of difficulties that TBI survivors faced. There are limited Asian studies on this clinical problem where socio-cultural factors are important in the coping with the disabilities.